The Cavendon luck [compact disc, unabridged] - Bradford, Barbara Taylor, 1933- (Bradford, Barbara Taylor, 1933- Cavendon chronicles., 2016)
Cavendon luck picks up nine years after Cavendon women, in July of 1938. Cecily and Miles, with the help of the whole family, have brought the family and the estate back from the brink of disaster. Now, with the arrival of World War II, Cavendon Hall will face its biggest challenge yet. Intrigue, romance, sorrow, and joy fill this epic saga as the Ingham and Swanns protect each other and the villagers and reveal their true capacity for survival and rebirth.